Care versus treatment: reflections on residential child care in Scotland - Laura Steckley (Scottish Journal of Residential Child Care)
'Residential treatment for adolescents' is a term used in the United States to describe something simultaneously similar to and completely different than residential child care in Scotland. This reflective article explores these similarities and differences.